Effects of an 8-Week Abdominal Hypopressive Technique Program on Pelvic Floor Muscle Contractility: An Assessor-Blinded Randomized Controlled Trial - Olga López-Torres; Miriam Álvarez-Sáez; Jorge Lorenzo Calvo; Loreto Carmona; Lidón Soriano (Applied Sciences)
Background: Pelvic floor muscle (PFM) dysfunctions, such as urinary incontinence (UI), significantly impact women’s quality of life. The abdominal hypopressive technique (AHT), a breathing and posture-based intervention, has emerged as a promising approach to improve PFM function. Despite growing evidence on its efficacy, limited research explores its effect on PFM contractility. Objective: This study aimed to evaluate the effects of an 8-week AHT program on pelvic floor muscle (PFM) strength in adult women with no prior experience with AHT. Methods: A randomized controlled trial was conducted with 42 females (mean age 43 ± 9 years) assigned to an experimental group (EG, n = 21) or a control group (CG, n = 21). The EG completed 24 AHT sessions (30 min/session, 3 sessions/week) over 8 weeks. PFM strength, measured via maximum voluntary contraction (MVC), was assessed pre- and post-intervention using the Phenix Biofeedback Kit. Secondary outcomes included load absorption and muscle efficiency. Muscle efficiency and load absorption were also registered. Results: After the 8-week intervention, significant improvements were observed in the EG for maximal voluntary contraction (MVC1 (from 672.2 ± 344.1 g/cm2 to 890.3 ± 435.8 g/cm2, p = 0.002) and load absorption (from 83.9 ± 36.8 to 103.1 ± 37.3, p = 0.001), with no significant changes in the CG. Between-group differences for MVC1 (p = 0.001), MVC2 (p = 0.016), and load absorption (p = 0.008) were statistically significant. High adherence (96%) and no adverse events were recorded. Conclusions: An 8-week AHT program significantly improved PFM strength, load absorption, and muscle efficiency in women from the present study comparing with the CG. AHT could be considered a safe, non-invasive, and effective intervention for pelvic floor rehabilitation, with potential benefits for addressing UI and enhancing pelvic floor functionality. Future research should focus on long-term outcomes and comparisons with alternative therapies.